2021
DOI: 10.3390/biology10010041
|View full text |Cite
|
Sign up to set email alerts
|

Cold Atmospheric Plasma, a Novel Approach against Bladder Cancer, with Higher Sensitivity for the High-Grade Cell Line

Abstract: Antitumor therapies based on Cold Atmospheric Plasma (CAP) are an emerging medical field. In this work, we evaluated CAP effects on bladder cancer. Two bladder cancer cell lines were used, HT-1376 (stage III) and TCCSUP (stage IV). Cell proliferation assays were performed evaluating metabolic activity (MTT assay) and protein content (SRB assay). Cell viability, cell cycle, and mitochondrial membrane potential (Δψm) were assessed using flow cytometry. Reactive oxygen and nitrogen species (RONS) and reduced glut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 73 publications
1
10
0
Order By: Relevance
“…Analysis of apoptosis-related genes, including BAX, BCL2, and CASP3, and also BAX/BCL2 ratio indicated CAP induces apoptotic pathway selectivity in tumor cells. Our results are in line with other studies that reported the effect of CAP on cytotoxicity and apoptosis in tumor cell lines [5,6,8,40,[43][44][45][46][47][48]. Other studies proved evidences that CUR has a cytotoxic effect and induces apoptosis in cancer cell lines [49][50][51][52][53][54][55][56].…”
Section: Discussionsupporting
confidence: 91%
“…Analysis of apoptosis-related genes, including BAX, BCL2, and CASP3, and also BAX/BCL2 ratio indicated CAP induces apoptotic pathway selectivity in tumor cells. Our results are in line with other studies that reported the effect of CAP on cytotoxicity and apoptosis in tumor cell lines [5,6,8,40,[43][44][45][46][47][48]. Other studies proved evidences that CUR has a cytotoxic effect and induces apoptosis in cancer cell lines [49][50][51][52][53][54][55][56].…”
Section: Discussionsupporting
confidence: 91%
“…In addition to the direct CAP strategy, CAP activity can also be transferred to liquids (i.e., plasma activated medium (PAM)), adding flexibility to the application of plasma therapy [4][5][6]. PAM, produced by activating culture medium with CAP, has been found to selectively cause a significant reduction in the viability of cancer cells, including breast cancer [7], bladder cancer [8], osteosarcoma [9], and skin cancer [10] cells.…”
Section: Introductionmentioning
confidence: 99%
“…The cold atmospheric plasma (CAP) operated at ambient temperature has attracted great interest in biomedical fields such as drug delivery and cancer therapy [23,24]. As one of common configurations, a plasma jet containing a high-voltage electrode and carrier gas is used to generate CAP for biomedical applications.…”
Section: Introductionmentioning
confidence: 99%